Modern Inquisitions : Peru and the Colonial Origins of the Civilized World - Silverblatt, Irene (Book collections on Project MUSE., 2004)
Trying to understand how "civilized" people could embrace fascism, Hannah Arendt searched for a precedent in modern Western history. She found it in nineteenth-century colonialism, with its mix of bureaucratic rule, racial superiority, and appeals to rationality. Modern Inquisitions takes Arendt's insights about the barbaric underside of Western civilization and moves them back to the sixteenth and seventeenth centuries, when Spanish colonialism dominated the globe. Irene Silverblatt describes how the modern world developed in tandem with Spanish imperialism and argues that key characteristics of the modern state are evident in the workings of the Inquisition. Her analysis of the tribunal's persecution of women and men in colonial Peru illuminates modernity's intricate "dance of bureaucracy and race." Drawing on extensive research in Peruvian and Spanish archives, Silverblatt uses church records, evangelizing sermons, and missionary guides to explore how the emerging modern world was built, experienced, and understood by colonists, native peoples, and Inquisition officials: Early missionaries preached about world history and about the races and nations that inhabited the globe; Inquisitors, able bureaucrats, defined who was a legitimate Spaniard as they executed heretics for "reasons of state"; the "stained blood" of Indians, blacks, and descendants of Jews and Moors was said to cause their deficient character; and native Peruvians began to call themselves Indian